Profiles of an image in the novels of Emilio Bacardi Moreau - Ana Vilorio-Iglesas (Santiago, 2016)
Emilio Bacardí Moreau is an indepted and prestigious intellectual burned in Santiago de Cuba, he is owner of a multifaceted piece that provide, even in our days, support to many researcher of different sciences. In consequence, the present article has the purpose of unveiling the value of its novels from the perspective of the resourceful utilization and caractereologic procedures for the achievement of his system of characters, appraised for important analysts of the humanistic matters. Actually those judgments are under consideration and others perspective are added on. His character’s design is a basic subsystem in its narrative, and was associated to the culture of the resistance of his epoch.